Genome-scale single-cell mechanical phenotyping reveals disease-related genes involved in mitotic rounding - Yusuke Toyoda (Nature Portfolio, 2017)
During cell division animal cells generate intracellular pressure and round against their environment, but the genes responsible for this are largely unknown. Here the authors use a microcantilever- and RNAi-based assay to screen > 1000 genes and identify 49 genes involved in mitotic cell rounding; many are novel to this process.